Talent in Judo: Conception of national team coaches - Junior, Jose Alfredo Olivio [UNESP]; Lopes, Marcos Antonio; Junior, Luiz Francisco Camilo [UNESP]; Mazzei, Leandro Carlos; Drigo, Alexandre Janotta [UNESP] (My University, 2024)
Background. Sports talent has often been presented in the literature. However, there is a lack of specific information for each sport. Problem and Aim. The purpose of this article was to identify what is the conception of sports talent and what characteristics should be observed in these individuals at the sport-specific level. Methods. Using a qualitative approach, 17 international judo coaches were interviewed. For data analysis, content analysis was used with an inductive approach. Results. Seven categories were identified grouped into two axes, “how the trainer identifies the talent” and “how the trainer develops the talent”. As for identification, “coach observation” followed by “competitive results” and “feedback from other coaches” were the main sources. Judo talent is conceptualized as complex and procedural, with multiple performance factors that can be synthesized as individuals who: have a technical repertoire (dominates several technical actions) associated with tactical skill (decision making). The condition for the development of these factors includes the following personal traits: motivation, ability and willingness to continue learning and willingness to work hard. Therefore, they are characteristics that coaches expect from judo talents. Conclusion. We were able to identify what is the concept of sporting talent in judo, highlighted mainly when it comes to personal aspects, such as tolerance for hard work, competitiveness and ability to learn. Technical quality was pointed out as the main aspect to be observed and developed, highlighting the variability of actions that an athlete is able to develop, and his ability to act and make decisions.
Keywords: coaches; identyfikacja talentów; judo; potencjał; potential; talent identification; trenerzy